Cation disorder and epitaxial strain modulated Drude–Smith type terahertz conductivity and Hall-carrier switching in Ca1−xCexRuO3 thin films. (14th November 2016) - Das, Sarmistha; Phanindra, V Eswara; Kumar, K Santhosh; Agarwal, Piyush; Dhaker, K C; Rana, D S
Abstract: The CaRuO3 is a non-Fermi liquid pseudo-cubic perovskite with a magnetic ground state on the verge of phase transition and it lies in the vicinity of the quantum critical point. To understand the sensitivity of its ground state, the effects of subtle aliovalent chemical disorder on the static and high frequency dynamic conductivity in the coherently strained structures were explored. The Ce-doped Ca1− x Ce x RuO3 (0 ⩽ x ⩽ 0.1) thin films were deposited on LaAlO3 (1 0 0) and SrTiO3 (1 0 0) substrates and studies for low-energy terahertz (THz) carrier dynamics, dc transport and Hall effect. These compositions exhibited a very effective and unusual Hall-carrier switching in both compressive and tensile strain induced epitaxial thin films. The dc resistivity depicts a switching from a non-Fermi liquid to a Fermi liquid behavior without any magnetic phase transition. A discernible and gradual crossover from Drude to Drude–Smith THz dynamic optical conductivity was observed while traversing from pure to 10% Ce-doped CaRuO3 films. Overall, a nearly Fermi liquid behavior, effective carrier switching and unusual features in THz conductivity, were all novel features realized for the first time in physically and/or chemically modified CaRuO3 . These new phases highlight the novel subtleties and versatility of the systems lying near the quantum critical point.